ChemInform Abstract: Structure and Chemical Bonding of ScNiB4. Issue 2 (14th January 2014) - Eickerling, Georg; Scherer, Wolfgang; Fickenscher, Thomas; Rodewald, Ute Ch.; Poettgen, Rainer
Abstract ScNiB4 is prepared by arc melting of stoichiometric mixtures of the elements followed by annealing slightly below the melting point for the growth of single crystals.